Influence of Special Additives in a Water Aerosol on the Suppression of a Forest Fire with it; Journal of Engineering Physics and Thermophysics; Vol. 91, iss. 5 - Antonov D. V. Dmitry Vladimirovich; Volkov R. S. Roman Sergeevich; Voytkov D. V. Ivan Sergeevich; Zhdanova A. O. Alena Olegovna; Kuznetsov G. V. Geny Vladimirovich (2018, 2018)
Title screen